Quantification of carbon emission and solid waste from pottery production by using life-cycle assessment (LCA) method in Yunnan, China - Li, Yang; Sharaai, Amir Hamzah; Ma, Sining; Wafa, Wafaurahman; He, Zhijian; Abdul Ghani, Latifah (MDPI, 2022)
Environmental pollution in the pottery industry is a severe problem, particularly dust and smoke pollution from the building-pottery industry. The main objectives of this study are to quantify the carbon emissions and solid-waste generation from the life cycle of pottery production in Yunnan. This study was carried out between November 2020 and May 2021. LCA was used, and 1 kg of pottery was used as the functional unit. There is a lot of literature to obtain data on the carbon emissions and solid waste generated in the process of pottery production for reference and calculation. This study forces the extraction of raw materials to the processing point, the device boundary of the pottery-production process. Carbon emissions in the pottery-production process account for about 80% of the whole pottery life cycle. Moreover, a large amount of solid waste is mainly produced as a result of the waste and production process. It is recommended that the serious pollution-causing combustion system should be reformed. The enterprise’s waste can be recycled. Most of the waste products can only be used as construction filling, and a small amount of the waste products can be used as hard materials in proportion after crushing.